Advanced motions for hexapods. (3rd April 2019) - Cheah, Wei; Khalili, Hassan Hakim; Arvin, Farshad; Green, Peter; Watson, Simon; Lennox, Barry
Advanced motions, which utilize footholds on walls, offer considerably more opportunities for hexapods in accessing confined environment. However, there has been no research on the practical application of such motions on a hexapod. These motions are kinematically viable for the standard hexapod design with three degrees of freedom per leg but the joint requirements have yet to be identified. This article presents the motion analysis for two forms of advanced motion, wall walking and chimney walking, to study the joint requirement for executing such motions. The analysis has been verified through a series of experiments demonstrating that a hexapod with a standard design is capable of executing advanced motions.